The influence of socio-demographic factors on the nutritional intake of overweight and obese children in the Stellenbosch area, Western Cape - Kirsten, Anna Petronella (Stellenbosch : Stellenbosch University, 2011)
Thesis (MNutr)--Stellenbosch University, 2011.